(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Aims and Objectives: A study was carried out to see the effects of chloroquine on the lungs of rats exposed to chloroquine during their intrauterine life. Type of Study : Descriptive cross sectional study Materials and Methods: In this study, 12 pregnant female albino rats were used and divided in 4 groups, A (control) and B,C and D (experimental). Total gestational period in rats ranges from 20-22 days which in this study was divided into three trimesters of seven days each. Oral dose of chloroquine 700mg/kg body weight was given to group B in first trimester (day1 to day 7), group C in 2nd trimester (day 8 to day 14) and group D in third trimester (day 15 to term). After the control and experimental groups had delivered, their offsprings were selected at random (about 5/adult rat). On day 5 after birth, lungs were then dissected out, processed, blocks were made, cut and mounted. Sections were stained with haemotoxylin and eosin stains Results: Histological sections of lungs of offsprings of group A showed typical normal histological structure of lungs. Microscopic sections of lungs of offsprings of group B showed no considerable change as compared to normal. Saccules and alveoli were mostly lined by type I pneumocytes. At some places type II pneumocytes and inflammatory cells were found. Interalveolar septum was thicker as compared to controls at few places. Histological sections of lungs of offsprings of C and D group showed that chloroquine reduced the expansion of saccules which normally occurred immediately preterm hence retarding foetal lung maturity. Saccular septa were much thicker and there was increased number of inflammatory cells in parenchyma. In offsprings of group D , saccular septa were the thickest and nearly all the saccules were lined by type II pneumocytes. Conclusion: In conclusion, chloroquine caused retardation of maturation of lungs in rats. So its use should be discouraged in pregnancy.